PERENCANAAN ARSITEKTUR SISTEM INFORMASI MENGGUNAKAN MODEL ENTERPRISE ARCHITECTURE PLANNING (EAP) di DIREKTORAT RESERSE KRIMINAL UMUM POLDA - Hilda Dwi Yunita (Universitas Bandar Lampung (UBL), 2018)
Lampung Police is primary implementer unit under Republic of Indonesian Police. It has some work units, one of them is General Crime Reserse Directory (Direskrimum) as unit of General Crime. Ditreskrimum doesn't has the exist planning for its development of information system, so its development just based on the current necessity that uncertain and it doesn't reach the optimal benefit. Based on that case, Direskrimum needs a blueprint about organization information like enterprise architecture. Enterprise Architecture Planning (EAP) is a method or concept to build an information architecture. EAP explains about datas architecture, application and technology for support the organizational business. Enterprise architecture form reffers to business function used to business with Police Report Revenue, Research and Investigation.